Notes on Life & Letters - Conrad, Joseph, 1857-1924 (Salt Lake City, UT : Project Gutenberg, 1997)
"Notes on Life & Letters" by Joseph Conrad is a collection of essays and reflections composed during the late 19th and early 20th centuries. The work encapsulates Conrad's insights into literature, critiques of various authors, and contemplations on life, reflecting on the intersection of literary creation and human experience. The essays range from appreciative observations about his literary predecessors, such as Henry James and Alphonse Daudet, to personal reflections on broader social and political themes. The opening portion of the collection begins with Conrad's author's note, where he humbly presents the essays as a personal tidying of his thoughts on literature and life. He describes the arrangement of these works as a mix of literary and political reflections over a span of two decades, conveying his view that art and intellectual expressions are intimately tied to the essence of human existence. Throughout this initial segment, Conrad emphasizes a sincere and contemplative approach to literary criticism, presenting both gratitude and introspection regarding the transient nature of literary endeavors and the artist's struggle for permanence amidst the inevitable decline of all things. The tone is both reflective and engaging, inviting readers to ponder the significance of literature in understanding human life. (This is an automatically generated summary.)
Letters: Books (1905). Henry James: an appreciation (1905). Alphonse Daudet (1898). Guy de Maupassant (1904). Anatole France (1904). Turgenev (1917). Stephen Crane: a note without dates (1919). Tales of the sea (1898). An observer in Malaya (1898). A happy wanderer (1910). The life beyond (1910). The ascending effort (1910). The censor of plays: an appreciation (1907) -- Life: Autocracy and war (1905). The crime of partion (1919). A note on the Polish problem (1916). Poland revisited (1915). First news (1918). "Well done" (1918). Tradition (1918). Confidence (1919). Flight (1917). Some reflections on the loss of the Titanic (1912). Certain aspects of the admirable inquiry (1912). Protection of ocean liners (1914). A friendly place.
Release date is 1997-12-01
Transcribed from the 1921 J. M. Dent edition by David Price
Keywords: Essays; Conrad, Joseph, 1857-1924; Literature -- History and criticism